Why Do People Want Dogs? A Mixed-Methods Study of Motivations for Dog Acquisition in the United Kingdom - Holland, Katrina E.; Mead, Rebecca; Casey, Rachel A.; Upjohn, Melissa M.; Christley, Robert M. (Frontiers in Veterinary Science, 2022)
With an estimated 12.5 million dogs in the UK alone, many people acquire a dog at some point during their lives. However, there are gaps in understanding about why UK owners decide to get dogs. Using a mixed-methods convergent design, this study identified the reasoning behind dog acquisition in a sample of UK current and prospective owners. An online survey of current (n=8,050) and potential (n=2,884) dog owners collected quantitative and qualitative data. Current owners were asked about the acquisition of their most recently acquired dog, whilst potential owners were asked about their dog ownership aspirations. Additional qualitative data were collected through semi-structured interviews with current (n=166) and potential (n=10) dog owners. Interviews focused on the factors that affected why and how people acquire dogs. Of survey responses, companionship for the respondent was the most common reason for wanting to get a dog, reported by 79.4% and 87.8% of current and potential owners, respectively. Facilitating exercise was reported as a reason for wanting to get a dog by 48.2% and 69.7% of current and potential owners, respectively. There were significant differences between current and potential owners in their likelihood of reporting pre-defined reasons, factors and influences involved in their decision to get a dog. Compared to current owners, potential owners were significantly more likely to report being motivated by most of the survey response options offered (including companionship for themselves or other adults in the household, helping a dog in need, lifestyle changes and previous experiences of meeting dogs), suggesting that current ownership status may affect experience and/or reporting expectations around dog ownership. Reflexive thematic analysis of qualitative data confirmed the importance of these motivations and identified additional reasons and factors that drive dog acquisition. These were organised into three overarching themes: Self-Related Motivation, Social-Based Motivation, and Dog-Related Positive Affect-Based Motivation. These findings provide insights into owners’ expectations of ownership which may inform the development of interventions to support potential owners’ decision-making around acquisition to maximise both dog and human welfare.